2021
DOI: 10.48550/arxiv.2102.07971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spin excitations coupled with lattice and charge dynamics in La$_{2-x}$Sr$_{x}$CuO$_4$

K. Ikeuchi,
S. Wakimoto,
M. Fujita
et al.

Abstract: Spin excitations of layered copper oxide show various characteristic features, depending on the carrier concentration. In this study, we conducted inelastic neutron scattering (INS) measurements on La2−xSrxCuO4 (LSCO), with x = 0, 0.075, 0.18, and 0.30 and La2−xSrxNiO4 (LSNO) with 1/3, to clarify the origin of the intensity enhancement in the excitation spectrum of LSCO at the energy (ω) of 16-19 meV [Phys. Rev. B 91, 224404 (2015), ibid. 93, 094416 (2016]. We confirmed the presence of a peak-structure in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(78 reference statements)
2
0
0
Order By: Relevance
“…Finally, we have found no evidence for interaction of the antiferromagnetic spin waves with phonons in the 15-20 meV range. Our results are consistent with another recent study that found such interactions in superconducting LSCO but not in LCO [47]. The interaction of phonons with spin stripes in hole-doped CuO 2 planes is an interesting problem that will need further study.…”
Section: Discussion and Summarysupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, we have found no evidence for interaction of the antiferromagnetic spin waves with phonons in the 15-20 meV range. Our results are consistent with another recent study that found such interactions in superconducting LSCO but not in LCO [47]. The interaction of phonons with spin stripes in hole-doped CuO 2 planes is an interesting problem that will need further study.…”
Section: Discussion and Summarysupporting
confidence: 93%
“…Our measurements also capture the antiferromagnetic spin waves. We check for a possible interaction between the spin waves and a low-energy optical mode of the type seen in Ba-and Sr-doped LCO [45,46], but find no evidence for such an interaction in the commensurate antiferromagnet, consistent with another recent neutron study [47].…”
Section: Introductionsupporting
confidence: 83%